2022
DOI: 10.3389/fbioe.2022.959210
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of a short-rod technique for lumbar fixation surgery

Abstract: Objective: The purpose of this study was to analyze the stability and instrument-related complications associated with fixation of the lumbar spine using the Short-Rod (SR) technique.Methods: Using finite element analysis, this study assessed the stability of a bilateral lumbar fixation system when inserting the pedicle screws at angles of 10°, 15°, and 20° to the endplate in the sagittal plane. Using the most stable construct with a screw angle, the model was then assessed with different rod lengths of 25, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
1
9
1
Order By: Relevance
“…Our results have suggested greater stress in the uncovertebral joint area, which could also explain the increased speed and quality of bone healing with bone grafting in the uncovertebral joint area during the short term. The method of immediate postoperative testing of biomechanical properties was adopted in most studies ( Wu et al, 2019 ; Huang et al, 2022 ; Liu et al, 2022 ; Lv et al, 2022 ; Zhang et al, 2022a ). Considering that osseointegration is a long-term process, a longer dynamic observation of the stress distribution in the region of the uncovertebral joint is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results have suggested greater stress in the uncovertebral joint area, which could also explain the increased speed and quality of bone healing with bone grafting in the uncovertebral joint area during the short term. The method of immediate postoperative testing of biomechanical properties was adopted in most studies ( Wu et al, 2019 ; Huang et al, 2022 ; Liu et al, 2022 ; Lv et al, 2022 ; Zhang et al, 2022a ). Considering that osseointegration is a long-term process, a longer dynamic observation of the stress distribution in the region of the uncovertebral joint is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, this study simplifies the musculoskeletal system, and the results under this ideal condition did not fully reflect the actual postoperative situation. Although this study aimed to provide a biomechanical reference for clinics, the manipulation of the muscular–ligamentous system in this finite analysis was based on previous literature ( Fu et al, 2022 ; Huang et al, 2022 ; Shen et al, 2022 ; Zhang et al, 2022b ). Last, linear elastic materials were adopted for the cervical vertebral body and intervertebral disc.…”
Section: Discussionmentioning
confidence: 99%
“…BPS-BMCS group offered the superior stability in extension and rotation, but in flexion and lateral bending. Huang et al [ 29 ] demonstrated that the inter-screw angle of 15° between the screw at the cranial and caudal segment resulted in the lowest L4-L5 segmental ROM in flexion, extension, and rotation. In this study, the inter-screw angle was 8° in the BPS-BMCS group and 33° in the BMCS-BPS group.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the 3-dimensional lumbar model used in this study, which was modified from a model previously developed by the research team (L4-L5) ( Huang et al, 2022 ). Some studies report the non-homogeneous property of vertebrae, but other studies also report the reliability of vertebrae being isotropic ( Hu et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Finite element model (FEM) analysis allows for one input factor such as the force or moment to be altered while keeping other factors constant. This is a convenient and inexpensive method of simulating different physiological conditions and has been widely used for assessing lumbar implants ( Yao et al, 2006 ; Huang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%